Pharmacological effects of PARP inhibitors on cancer and other diseases - Guaman Ortiz, L. (2011)
Poly(ADP-ribosylation), a post-translational modification of proteins involved in DNA repair, replication, transcription and cell death, consists in the conversion of -NAD + into ADP-ribose, and the further formation of polymers of variable length and structure bound to nuclear protein acceptors. Polymer synthesis and degradation are performed respectively by poly(ADP-ribose) polymerase (PARP) and poly(ADP-ribose) glycohydrolase (PARG) enzymes. Poly(ADP-ribosylation) represents an emergency reaction to DNA damage; however, PARP overactivation promotes NAD depletion and consequent necrosis, thus exerting a noxious function in many circumstances. The search for chemical compounds able to inhibit poly(ADP-ribosylation) allowed the discovery of new molecules and potent derivatives. Pharmacological inhibition of PARP enzymes is able to reverse the deleterious NAD consumption, thus having a protective role towards many pathological conditions. Of note, the combined treatment of tumors with PARP inhibitors and anticancer drugs has been shown to have a beneficial effect in anticancer therapy. On the whole, pharmacological inactivation of poly(ADP-ribosylation) represents a novel therapeutic strategy to limit cellular injury and to improve the prognosis of a variety of diseases. © 2011 Bentham Science Publishers.